Педагогічні видання, підручники та посібники для економічної освіти дітей і дорослих (західноукраїнські землі ХІХ – початку ХХ ст.) - Гіптерс, Зінаїда (Видавництво Львівської політехніки, 2012)
В статье рассматривается педагогическая, культурно-просветительная деятельность украинских общественных организаций и педагогов, их роль в деле подготовки педагогических изданий, учебников и методических пособий для экономического образования детей и взрослых на западноукраинских землях ХІХ – начала ХХ в. The author considers pedagogical, cultural and educational activity of Ukrainian social organizations and teachers, their role in the process of preparation of pedagogical issues, textbooks and manuals for economic education of children and adults in West Ukraine in the XIXth – in the beginning of the XXth centuries.
Педагогические издания, учебники и методические пособия для экономического образования детей и взрослых (западноукраинские земли ХІХ – начала ХХ в.)
Pedagogical issues, textbooks and manuals for economic education of children and adults (West Ukraine in the XIX – in the beginning of the XX cthenturies)
Keywords: экономическое образование детей и взрослых; кооперация; профессиональное образование; культурно-просветительные организации; общества “Просвита”, “Ридна школа”, “Сельский господарь”; Ревизионный Союз Украинских Кооперативов; economic education of children and adults; cooperation; vocational education; cultural and educational organizations; “Prosvita”; “Ridna Shkola”; “Selskyi hospodar”; Revisionary Union of Ukrainian Cooperatives